Molecular characterization of the beta(2)-like octopamine receptor of helicoverpa armigera - Gujar, Nidhi; Nikte, V, Siddhanta; Joshi, Rakesh S.; Joshi, Manali (Journal of Membrane Biology, 2021)
Helicoverpa armigera is a devastating polyphagous and cosmopolitan crop pest. There are reports of this insect being resistant to a variety of pesticides raising concern worldwide. The Octopamine (OA) binding beta(2)-like receptor (OAR), a GPCR, is widely distributed in the nervous system of the insect and plays essential roles in the physiology and development and thus is an important target for insecticides. Yet, the molecular characterization of the H. armigera OAR (HarmOAR) and rational design of compounds based on this receptor is lacking. As a first step, we performed multiple sequence alignment of all insect OARs, which revealed that the sequences contained all conserved class A GPCR motifs. Phylogenetic studies showed clade-specific variations in the protein sequences primarily arising owing to differences in the ICL3 loop region. Further, a structural model of HarmOAR was built using the inactive human beta(2)AR as a template. 0.9 mu s atomistic simulations revealed conserved inter helical contacts and water molecules of HarmOAR. The detailed binding of octopamine was studied using molecular docking and 0.3 mu s atomistic simulations. Twenty-two insecticides active against octopamine receptors of other insects were compiled and docked to HarmOAR followed by rescoring with binding free energies to prioritize them for H. armigera. Our study suggests alpha-terpineol to be a good candidate as an insecticide or insect repellent for Helicoverpa armigera.
Keywords: docking; Helicoverpa armigera; Insecticides; molecular dynamics; Octopamine receptor; Phylogeny

Noncanonical regulation of the plasma membrane copper transporter CTRL through modulation of membrane mechanical properties - Chatterjee, Subhendu K.; Kar, Sumanta; Nikte, V, Siddhanta; Dash, Tisha; Ghosh, Tanmoy; Paul, Mrittika; Maji, Saptarshi; Sengupta, Durba; Sinha, Bidisha; Gupta, Arnab (Molecular Biology of the Cell, 2026)
We describe a noncanonical, membrane receptor-like regulation of the human copper transporter-1 (CTR1) in response to copper stimuli. CTR1 is the sole high-affinity trimeric plasma-membrane copper-importing channel that self-regulates by undergoing endocytosis to limit copper uptake. We observed that preceding copper-induced endocytosis, CTR1 forms clusters on the plasma membrane, a phenomenon that is typically observed in membrane receptors. We deciphered the mechanism of CTR1 clustering and studied its ramifications on the physical properties of plasma membranes harboring these clusters that could favor endocytosis. Membrane tension and fluctuation are fundamental regulators of pre-and post-endocytic events. Using coarse-grain molecular dynamics (MD)-simulations and coupled interference reflection microscopy-total internal reflection fluorescence microscopy (TIRF) we demonstrated that CTR1 clusters induce positive membrane curvature, an increase in local membrane tension, and a decrease in local membrane fluctuation; alterations that favor the formation of endocytic pits. Clustering is facilitated by copper sequestering methionine-rich extracellular amino-terminus of CTR1. MD-simulations and IRM-TIRF imaging revealed that CTR1 clustering is facilitated by membrane cholesterol, depletion of which delays CTR1 endocytosis. CTR1 clustering promotes clathrin-coated pit formation that engages recruitment of adaptor protein AP-2. To summarize, we report hitherto unknown ``pre-endocytic'' ``receptor-like'' phenomenon of ligand-induced clustering of a metal channel, which in turn regulates self-endocytosis by modulating membrane properties.